AUTONOMOUS MOTIVATION OF PROTAGONIST’S SELF DETERMINATION IN NICHOLAS SPARKS’ THE BEST OF ME - Irma Oktia Waila; Sri Wulan (JOURNAL OF LANGUAGE, 2021)
Nicholas Sparks’ The Best of Me is a novel that tells the story of a love journey between Dawson Cole and Amanda Collier, who is forced to be blocked by Amanda's parents who do not approve of their love because of differences in social class so that in the end they have to separate. However, after being separated for so long they are reunited with different circumstances. The strength of this novel is the moral value of the main character. This study aims to examine the self-determination that exists in the protagonist. In examining this novel, the writers adopt descriptive qualitative research. There two forms of self-determination. They are autonomous motivation and controlled motivation. The study is focused only on the autonomous motivation of the protagonist’s self determination in the novel. Two aspects are found as the protagonist’s autonomous motivation. These aspects happen to the protagonist’s love story in the novel. The first is loyalty and the second firmness of love. The protagonist shows his self-determination by means of two aspects.